凝血酶敏感蛋白-1与口腔颌面部恶性肿瘤发生发展的关系 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2018)
Thrombospondin-1 (TSP-1) is widely distributed in human tissues and is important in inhibiting angiogenesis.It also occupies an indispensable position in the formation, growth, differentiation, and metastasis of tumors in different tissues.TSP-1 plays an important role in the occurrence and development of various types of tumors. The inhibitory effect of TSP-1 on the angiogenesis and tumor development of oral and maxillofacial malignant tumors has been demonstrated in recent years. This paper reviews the findings and progress of TSP-1 research involving all kinds of tumors as well as oral and maxillofacial malignancies.